2018
DOI: 10.3390/ijms19123708
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase-Induced Phosphorylation of MET is Significantly Associated with Poor Prognosis in Invasive Bladder Cancer; an Immunohistochemical Analysis

Abstract: Hepatocyte growth factor (HGF) plays an important role in cancer progression via phosphorylation of MET (c-met proto-oncogene product, receptor of HGF). HGF-zymogen (pro-HGF) must be processed for activation by HGF activators including matriptase, which is a type II transmembrane serine protease and the most efficient activator. The enzymatic activity is tightly regulated by HGF activator inhibitors (HAIs). Dysregulated pro-HGF activation (with upregulated MET phosphorylation) is reported to promote cancer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Increased phosphorylation of Tyr1234/1235 (at activation loop) and Tyr1349 (at multi-docking site) was positively correlated with pT stage, and multivariate analysis prompted the authors to conclude that phosphorylated Tyr1349 was a significant predictive factor of pT stage only. In addition, phosphorylated Tyr1349 was correlated with expression of matrix metalloprotease (MMP)-2, MMP-7, and E-cadherin [98]. Furthermore, the relationship between increased phosphorylation of Tyr 1235 in MET and worse cancer-specific survival in patients with muscle invasive bladder cancer (MIBC) was reported by Yamasaki et al In this study, increased expression of matriptase and decreased expression of HAI-1 were also correlated with poor prognosis [99].…”
Section: Significance Of Hgf-dependent Met Activation In Muscle Invassupporting
confidence: 60%
See 3 more Smart Citations
“…Increased phosphorylation of Tyr1234/1235 (at activation loop) and Tyr1349 (at multi-docking site) was positively correlated with pT stage, and multivariate analysis prompted the authors to conclude that phosphorylated Tyr1349 was a significant predictive factor of pT stage only. In addition, phosphorylated Tyr1349 was correlated with expression of matrix metalloprotease (MMP)-2, MMP-7, and E-cadherin [98]. Furthermore, the relationship between increased phosphorylation of Tyr 1235 in MET and worse cancer-specific survival in patients with muscle invasive bladder cancer (MIBC) was reported by Yamasaki et al In this study, increased expression of matriptase and decreased expression of HAI-1 were also correlated with poor prognosis [99].…”
Section: Significance Of Hgf-dependent Met Activation In Muscle Invassupporting
confidence: 60%
“…In addition, phosphorylated Tyr1349 was correlated with expression of matrix metalloprotease (MMP)-2, MMP-7, and E-cadherin [97]. Furthermore, the relationship between increased phosphorylation of Tyr 1235 in MET and worse cancer-specific survival in patients with muscle invasive bladder cancer (MIBC) was reported by Yamasaki et al In this study, increased expression of matriptase and decreased expression of HAI-1 were also correlated with poor prognosis [98]. Interestingly, the area of HAI expression and MET phosphorylation presented reciprocally in spite of the strong expression of both total MET and matriptase ( Figure 6b) [98].…”
Section: Significance Of Hgf-dependent Met Activation In Muscle Invassupporting
confidence: 59%
See 2 more Smart Citations
“…With respect to the pathological significance of c-Met phosphorylation in cancers, a previous report demonstrated that the expression of phospho-c-Met (Y1349), termed pY1349 c-Met, is positively associated with cancer growth, progression, and poor survival in patients with RCC (18). Likewise, one report indicated that high pY1235 c-Met expression is associated with an increased risk of recurrence for ovarian cancer patients (24); meanwhile, in patients with BC, several reports have shown that phosphorylated c-Met leads to highly malignant disease and poor survival (25,26). However, the precise pathological significance of phosphorylated c-Met in BC is not fully understood.…”
Section: Introductionmentioning
confidence: 99%